Utilization of Social Media in the Implementation of the West Java Governor Program - Muchamad Difa, Fredyan Davice; Permatasari, Ane (Faculty of Social Science, Universitas Negeri Semarang, 2023)
This study aims to analyze the use of social media in Ridwan Kamil's work implementation program as Governor of West Java. It is known that Ridwan Kamil produced many work programs as Governor of West Java. In its policy, there are several programs created based on social media. The type of research used in this study is a qualitative-descriptive approach, with the technique used to analyze the data, namely the content analysis method, with the help of Nvivo 12 Plus software. This technique is used to conclude objectively and systematically through the findings or observations of object behavior. The research method used by researchers is a case study. The results showed that Ridwan Kamil could utilize social media to realize his vision and mission as Governor of West Java. Many programs are created based on social media as a public service, both on Twitter and on applications. One program that is considered very effective is Sapawarga. Ridwan Kamil did this to achieve efficiency in its performance. Social media allows people to access these public services anytime and anywhere. However, on the other hand, there is a weakness: some have decreased social media interaction, so some are no longer active.